The Role of Media Literacy on The Phenomenon of Digital Loneliness (Case Study on Students in The City of DI.Yogyakarta) - Wedadjati , Ratna Sesotya; Apandi; Lestari , Intan Fuji; Helmi, Sulaiman (SMARTINDO, 2024)
Purpose - This study aims to explore the phenomenon of digital loneliness among students in Yogyakarta and understand the role of media literacy in reducing the negative impacts of digital loneliness. Design/methodology/approach - This study uses a qualitative approach with a case study method, involving in-depth interviews with 17 students selected based on inclusion criteria. Interview questions were designed to examine the level of media literacy of students and its impact on the experience of digital loneliness. Findings and Discussion - The results of the study indicate that most students have a good understanding of media literacy, which helps them navigate information in digital media more critically. However, digital loneliness remains a challenge that affects their mental health, with effects on anxiety, stress, and decreased academic productivity. Students who have better media literacy tend to be able to reduce feelings of digital loneliness through more meaningful content selection and interactions. Conclusion - Media literacy plays an important role in helping students overcome digital loneliness. It is hoped that educational institutions can improve media literacy through training and creating wider opportunities for direct social interaction. This will help students manage their use of social media wisely and support their emotional well-being.